Factor and sketch polynomials - Pol...
Factor and sketch polynomials - Polynomials Part 1

Factorization of Cubic Polynomial 

We at ask-math believe that educational material should be free for everyone. Please use the content of this website for in-depth understanding of the concepts. Additionally, we have created and posted videos on our youtube.

We also offer One to One / Group Tutoring sessions / Homework help for Mathematics from Grade 4th to 12th for algebra, geometry, trigonometry, pre-calculus, and calculus for US, UK, Europe, South east Asia and UAE students.

Affiliations with Schools & Educational institutions are also welcome.

Please reach out to us on [email protected] / Whatsapp +919998367796 / Skype id: anitagovilkar.abhijit

We will be happy to post videos as per your requirements also. Do write to us.

In this section, we will discuss Factorization of Cubic Polynomial.

The degree of the cubic (highest exponent) polynomial is 3.
There are different identities in Factorization of Cubic Polynomial .
They are as follows :
1) a3 + b3 + 3a2b + 3b2a = (a + b)3

2) a3 - b3 - 3a2b + 3b2a = (a - b)3

3) a3 + b3 = (a + b)(a2 - ab + b2)

4) a3- b3 = (a - b)(a2 + ab + b2)

5) a3 + b3+ c3- 3abc
= (a + b + c)(a2 + b2+ c2 - ab - bc - ac)


6) If a + b + c = 0 then a3 + b3+ c3=3abc

Using Identities

Examples :

1)27x3- 8

Solution :
As first term and the 2nd term are perfect cube, we use the identity of cube

(a3 - b3) = ( a - b)(a2 +ab + b2)

a = 3x and b = 2

27x3- 8 = (3x -2)[(3x)2 + 6x + 22)]

= (3x -2)(9x2 + 6x + 4)are the factors.

________________________________________________________________
2) 8x3 +1

Solution :
As first term and the 2nd term are perfect cube, we use the identity of cube

(a3 + b3) = ( a + b)(a2 -ab + b2)

a = 2x and b = 1

8x3+ 1 = (2x + 1)[(2x)2 - 2x + 12)]

= (2x +1 )(4x2 - 2x + 1)are the factors.

________________________________________________________________
3) 27x3 + y3 + 9x2y + 3xy2

Solution :
As in the given equation there are two perfect cubes, so we can use 1st identity.

27x3 + y3 + 27x2y + 9xy2

= (3x)3 + (y)3 + 3(3x)2y + 3(3x)y2

= (3x + y)3 [ here a = 3x and b= y;a3 + b3 + 3a2b + 3b2a = (a + b)3 ]

_______________________________________________________________
4) (1.5)3 - (0.9)3 - (0.6)3

Solution :
(1.5)3 - (0.9)3 + (-0.6)3

Let a = 1.5, b = - 0.9 and c = -0.6

As a + b + c = 1.5 + 0.9 - 0.6 = 0

a3 + b3+ c3 = 3abc

= 3(1.5)(- 0.9)(-0.6)

= 2.430




Factoring

Factorization by common factor
Factorization by Grouping
Factorization using Identities
Factorization of Cubic Polynomial
Solved Examples on Factorization

Home Page